Mental Language : From Plato to William of Ockham - Panaccio, Claude, 1946- (Book collections on Project MUSE., 2017)
This book offers a history of the idea that human thought is structured like a language, from Plato and Aristotle up to the fourteenth century when William of Ockham gave it a new importance and developed it in a systematic way.